2015
DOI: 10.1007/s10597-015-9848-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Social Isolation Among Caregivers of Adults with Schizophrenia: Policy and Outcomes

Abstract: Services have been increasingly directed at supporting carers of people living with mental illness but it is difficult to evaluate the impact of service change where benchmarks for carer functioning are sparse. Sixty Australian carers were assessed regarding their quality of life, psychological distress, social isolation and caregiving experience. Their scores were compared with two matched community samples and previous studies. Carers were ten times more likely to be socially isolated and quality of life was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 23 publications
10
89
0
5
Order By: Relevance
“…Recently published evidence indicates they are up to 10 times more isolated than non-carers but are also significantly more socially isolated than carers of people with other health conditions. [6][7][8] Poor levels of physical health, including sleep difficulties,…”
Section: Challenges Faced By Carersmentioning
confidence: 99%
“…Recently published evidence indicates they are up to 10 times more isolated than non-carers but are also significantly more socially isolated than carers of people with other health conditions. [6][7][8] Poor levels of physical health, including sleep difficulties,…”
Section: Challenges Faced By Carersmentioning
confidence: 99%
“…Psychosis in a family member can be associated with high levels of stigma and shame (McCann, Lubman, & Clark, ; Wasserman, de Mamani, & Suro, ) and feelings of desperation (Allard, Lancaster, Clayton, Amos, & Birchwood, ). Social isolation in carers is high with recent evidence suggesting they were 10 times more isolated than non‐carers (Hayes, Hawthorne, Farhall, O'Hanlon, & Harvey, ). The caregiving role is commonly linked to high levels of burden, stress and distress (Lavis et al, ) which is significantly higher in early psychosis populations (Addington, Coldham, Jones, Ko, & Addington, ; Boydell et al, ) and can persist over the illness course (Brown & Birtwistle, ; Poon, Harvey, Mackinnon, & Joubert, ).…”
Section: Introductionmentioning
confidence: 99%
“…The types of support include: needing information regarding illness, services and management of the illness, support to improve relationships between carers and those for whom they care, and emotional support to talk about their experiences (Cleary, Freeman, Hunt, & Walter, ; Coker, Williams, Hayes, Hamann, & Harvey, ). In addition, caregivers typically experience social isolation, poor psychological health and diminished quality of life (Awad & Voruganti, ; Hayes, Hawthorne, Farhall, O'Hanlon, & Harvey, ). Studies have indicated that higher levels of perceived unmet needs had a negative effect on carers’ quality of life and extent of care‐giving impact (Cleary, Hunt, Walter, & Freeman, ; Zahid & Ohaeri, ).…”
Section: Introductionmentioning
confidence: 99%